JS04.5.A Enhancing the activity of anti-CD47 antibody therapy with radiotherapy in preclinical models of medulloblastoma. (5th September 2022) - Abbas, Z; Howlett, M; Buck, J; Hii, H; Kuchibhotla, M; Ancliffe, M; Whitehouse, J; Johns, T; Ebert, M; Gottardo, N; Endersby, R
Abstract: Background: Brain cancers are the most common solid cancer in children and the leading cause of cancer-related deaths in children. Medulloblastoma is the most common paediatric brain tumour. Treatment for medulloblastoma involves surgery, craniospinal irradiation (CSI) and chemotherapy. These therapies are extremely damaging to the developing brain and have not changed in decades, resulting in stagnation in the survival outcomes for children with medulloblastoma, and poor quality of life for children who survive their treatment. Immunotherapy has become a focus of novel treatment development. While there are multiple clinical trials aiming to increase immune recognition of medulloblastoma, none have been successful to date. Anti-CD47 is an immune-modulating therapeutic antibody which blocks the anti-phagocytic signal, CD47, expressed by brain cancer cells. Anti-CD47 has shown promising preliminary efficacy in brain cancer models. Material and Methods: Using a small animal radiotherapy platform, we have developed a preclinical CSI protocol which mimics clinical radiotherapy. Using an orthotopic xenograft model of medulloblastoma, mice were treated with either anti-CD47 antibody therapy, CSI, or the combination of both anti-CD47 and CSI. Results: CSI was found to deplete adaptive immune cells in the brain, while myeloid cells remained the dominant populations. Anti-CD47 antibody therapy was ineffective as a single agent against a patient derived xenograft model of Group 3 medulloblastoma, and CSI as a monotherapy resulted in temporary tumour regression. We found that the combination of anti-CD47 with CSI resulted in marked and persistent tumour regression. Conclusion: This preclinical work has shown promising efficacy of anti-CD47 in combination with CSI, which we are currently testing in additional models. Our work is currently employing a range of techniques such as high dimensional flow cytometry and single cell sequencing to elucidate the mechanisms by which radiotherapy enhances the anti-tumour activity of myeloid cells. This work will enable the rational design and translation of optimal combination therapies for medulloblastoma clinical trials.